Top secret twenty-one [large type] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2014)
Stephanie Plum is back in an all-new adventure from #1 bestselling author Janet Evanovich. This time Stephanie's in deep. To get to the bottom of the mess, she's going to have to keep things "Top Secret."